ANALISIS NILAI-NILAI KEMANUSIAAN DALAM FILM DEAR NATHAN KARYA ERISCA FEBRIANI - Irwan Soulisa; Frenny Silvia Pormes; Peter Manuputty (SOSCIED, 2022)
This study examines human values ​​in the film Dear Nathan by Erisca Febriani. The purpose of this study is to describe in depth the human values ​​contained in the Dear Nathan film by Erica Febriani. The method used in this research is qualitative method. The formulation of the problem how are the human values ​​contained in the film Dear Nathan Erisca by Febriani Erisca Febriani?. The data source is the film Dear Nathan Erisca by Febriani Erisca Febriani. Data collection techniques are watching techniques, listening techniques and note-taking techniques. Data analysis techniques include three components, namely: (1) data reduction (2) data presentation, (3) drawing conclusions. In conclusion, the Dear Nathan film by Erisca Febriani, there are 5 human values, namely: (1) the value of truth (2) the value of peace (3) the value of love or compassion (4) the value of right behavior or virtue, and (5) the value of non-violence